A double ITCZ phenomenology of wind errors in the equatorial Atlantic in seasonal forecasts with ECMWF models - Shonk, Jonathan KP; Demissie, Teferi Dejene; Toniazzo, Thomas (Copernicus GmbH, 2019)
Modern coupled general circulation models produce systematic biases in the tropical Atlantic that hamper the reliability of long-range predictions. This study focuses on a common springtime westerly wind bias in the equatorial Atlantic in seasonal hindcasts from two coupled models – ECMWF System 4 and EC-Earth v2.3 – and in hindcasts also based on System 4, but with prescribed sea-surface temperatures.